2013
DOI: 10.1111/ans.12251
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related sclerosing cholangitis: the cholangiocarcinoma mimic

Abstract: A 51-year-old woman presented with a 3-week history of painless obstructive jaundice on a background of diet-controlled type 2 diabetes mellitus and significant weight loss. There was no history of inflammatory bowel disease. Physical examination revealed cachexia and jaundice. Relevant blood tests showed bilirubin, 56 μmol/L; alkaline phosphatase 1069 IU/L; gamma-glutyamyltransferase, 1114 IU/L; raised carbohydrate antigen 19-9 level, 213 kU/L; and normal carcinoembryonic antigen level, 2.1 ng/mL.Ultrasound s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Common examples are round or wedge-shaped renal cortical lesions, peripheral cortical nodules, mass-like lesions, and pelvic wall thickening in the kidneys; soft-tissue masses surrounding the aorta and its branches in the retroperitoneum and mesentery; and lymphadenopathy [41][42][43][44]. An imaging diagnosis of ISC becomes highly challenging in patients with no recognizable lesion in other organs [45,46]. The image findings useful for the diagnosis of ISC include multifocal biliary strictures, a markedly thickened bile duct wall (mean wall thickness, 4.9 mm), a smooth outer margin, a narrow but visible lumen, hyperenhancement during the late arterial phase, homogeneous hyperenhancement during the delayed phase, concurrent gallbladder wall thickening, and no vascular invasion (Fig.…”
Section: Ct/mrmentioning
confidence: 99%
“…Common examples are round or wedge-shaped renal cortical lesions, peripheral cortical nodules, mass-like lesions, and pelvic wall thickening in the kidneys; soft-tissue masses surrounding the aorta and its branches in the retroperitoneum and mesentery; and lymphadenopathy [41][42][43][44]. An imaging diagnosis of ISC becomes highly challenging in patients with no recognizable lesion in other organs [45,46]. The image findings useful for the diagnosis of ISC include multifocal biliary strictures, a markedly thickened bile duct wall (mean wall thickness, 4.9 mm), a smooth outer margin, a narrow but visible lumen, hyperenhancement during the late arterial phase, homogeneous hyperenhancement during the delayed phase, concurrent gallbladder wall thickening, and no vascular invasion (Fig.…”
Section: Ct/mrmentioning
confidence: 99%
“…Six patients presented with obstructive jaundice as the main clinical manifestation [1116] and others presented with varied clinical symptoms [1728]. Gastrointestinal bleeding was not reported in any of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-SC has been described in radiology and clinical literature as having certain suggestive radiologic features [4,5], but also demonstrating overlap with hilar and extrahepatic cholangiocarcinoma (CCA), as well as primary sclerosing cholangitis (PSC) [69]. Case reports [10] and experience at our institution have shown that differentiating between IgG4-SC and CCA can be difficult radiologically and clinically, which can lead to challenges in patient management.…”
Section: Introductionmentioning
confidence: 99%